SYNJ1 rescues motor functions in hereditary and sporadic Parkinson's disease mice by upregulating TSP-1 expression - Tian, Yueqin; Yi, Shang; Guo, Wanyun; Feng, Cuilian; Zhang, Xiufen; Dong, Huateng; Wang, Kaitao; Li, Runtong; Tian, Yuanxin; Gan, Min; Wu, Ting; Xie, Haiting; et al. (Behavioural brain research, 2023)
This study aimed to explore the role of SYNJ1 in Parkinson's disease (PD) and its potential as a neuroprotective factor. We found that SYNJ1 was decreased in the SN and striatum of hSNCA*A53T-Tg and MPTP-induced mice compared to normal mice, associated with motor dysfunction, increased α-synuclein and decreased tyrosine hydroxylase. To investigate its neuroprotective effects, SYNJ1 expression was upregulated in the striatum of mice through injection of the rAdV-Synj1 virus into the striatum, which resulted in the rescue of behavioral deficiencies and amelioration of pathological changes. Subsequently, transcriptomic sequencing, bioinformatics analysis and qPCR were conducted in SH-SY5Y cells following SYNJ1 gene knockdown to identify its downstream pathways, which revealed decreased expression of TSP-1 involving extracellular matrix pathways. The virtual protein-protein docking further suggested a potential interaction between the SYNJ1 and TSP-1 proteins. This was followed by the identification of a SYNJ1-dependent TSP-1 expression model in two PD models. The coimmunoprecipitation experiment verified that the interaction between SYNJ1 and TSP-1 was attenuated in 11-month-old hSNCA*A53T-Tg mice compared to normal controls. Our findings suggest that overexpression of SYNJ1 may protect hSNCA*A53T-Tg and MPTP-induced mice by upregulating TSP-1 expression, which is involved in the extracellular matrix pathways. This suggests that SYNJ1 could be a potential therapeutic target for PD, though more research is needed to understand its mechanism.